Epidemiological study of epidemics of the measles in Al – Najaf city for the period from 1/4/2008 to 1/8/2009 - Abeed, Shatha A. (Al-Qadisiyah Journal of Pure Science, 2017)
This study was carried in Al – Najaf city for period from 1/4/2008 for 1/8/2009 to show the epidemics of the measles infection among patients were admitted to Al- Hakim general hospital . The relevant information was collected from records of the hospital & patients sheets . There were 1648 patients ( males & females ) . It was found that the majority of the disease occurred in age of the patients between ( 1 – 10 years old ) ( 48.5 % ) , followed by age between ( 11 – 20 years old ) ( 20.12 % ) , then age between ( 1 month – less than 1 year old ) ( 15.3 % ) . The number of admitted cases was nearly equal for both sexes. ( 59.5 % ) of cases were from rural areas , while the remainder ( 40.5 %) from urban areas . There are several complications associated with measles in this study like pneumonia ( 91.5 % ) , followed by enteritis & diarrhea ( 4.4 % ) , then bronchitis ( 3.8 % ) & finally encephalitis ( 0.3 % ) .